Role of oral examination in newly diagnosed multiple myeloma patients: A safe and simple way to detect light chain amyloidosis. (5th July 2018) - Leiba, Merav; Jarjoura, Suha; Abboud, Waseem; Nagler, Arnon; Yahalom, Ran; Duek, Adrian; Yarom, Noam
Abstract: Objective: Up to 30% of multiple myeloma (MM) patients have subclinical amyloid deposits. These patients are under‐recognized and are more susceptible to drug toxicity, bleeding and death. Early diagnosis and adjustment of treatment are crucial. Biopsies of oral mucosa might be a potentially useful diagnostic tool. The objective of this study was to assess the prevalence and characteristics at presentation of oral amyloidosis in a large cohort of MM patients. Methods: The prevalence and characteristics of oral amyloidosis in a large cohort of MM patients who were referred for oral evaluation before and during bisphosphonate therapy were assessed, retrospectively. Results: Among 212 patients analysed, 13 (6%) were diagnosed with concomitant light chain (AL) amyloidosis. In 54% ( n = 7), lesions in the oral cavity compatible with amyloid deposition were detected by examination. Conclusions: The salient feature of this study is the high prevalence of oral manifestations among MM patients with amyloidosis. These results highlight the value of routine oral cavity examination and biopsy as a safe and simple method for detecting light chain amyloidosis.